Spinning continuous high-strength bacterial cellulose hydrogel fibers for multifunctional bioelectronic interfaces. Issue 21 (23rd May 2021) - Zhang, Minghao; Chen, Shiyan; Sheng, Nan; Wang, Baoxiu; Wu, Zhuotong; Liang, Qianqian; Han, Zhiliang; Wang, Huaping
Abstract : The realization of the reconciliation of contradictory multi-properties required for hydrogel fibers as bioelectronic interfaces. Abstract : Ionic conductive hydrogel fibers have attracted much attention as ideal optoelectronic physiological probes. However, their application is limited by their biocompatibility problem caused by the dependence on high-concentration ions, poor mechanical properties due to swelling, and continuous preparation. Here, we prepared a pure natural bacterial cellulose hydrogel fiber (BCHF) by a simple continuous wet-spinning method without any additional cross-linking step. The hydrogel fiber exhibits an excellent tensile strength of 3.74 MPa as well as a high-water content of 87% with no swelling properties. It can also maintain 90% of its original strength after being soaked in water for 14 days. The hydrogel fiber also integrates good bio-ion conductivity and light-guiding performance, and it can be directly used as a pure natural nanofluidic device without packaging for the detection of trace neurotransmitters. The strategy of achieving multifunctional hydrogel fibers will open up a new route for the development of next-generation neural interfaces.